Terapi JalÄ NetÄ« sebagai Upaya Pembersihan Saluran Pernapasan Hidung - Wiyana, Yoga; Juniartha, Made G. (JURNAL YOGA DAN KESEHATAN, 2021)
The nose is a vital respiratory organ that has a role as the first organ that protects the body in the respiratory tract against microorganisms and other harmful substances that are inhaled along with the entry of air. Therefore, nasal hygiene is something that needs to be considered, especially if there are disturbances. One way that can be done is by means of JalÄ NetÄ« therapy. JalÄ NetÄ« therapy or nasal cleansing is a simple technique that can be used to treat symptoms of problems or diseases that occur in the nasal cavity. JalÄ NetÄ« therapy or nasal cleansing has benefits if done properly. JalÄ NetÄ« is part of the six body cleansing techniques in Hatha Yoga called ShatkarmÄ. There are four main texts of Hatha Yoga that describe JalÄ NetÄ« including Hatha Yoga Pradipika, Gheranda Samhita, Shiva Samhita and Hatharatnavali. JalÄ NetÄ« is performed by flowing warm water mixed with a little salt (Lavan JalÄ) from one nostril to the other using a specially designed pot or tool. JalÄ NetÄ« has a cleansing effect on the nasal cavity by removing the remaining dirt and microorganisms in the nasal cavity and providing healing therapy for disorders or diseases of the nasal respiratory tract.